Design and Wind Tunnel Testing of Funnel Based Wind Energy Harvesting System. (2015) - Kumar, Nallapaneni Manoj; Subathra, M.S.P.; Cota, Orville Damaso
Abstract: Modern wind energy systems are of giant structures having a turbine generator on the top of tower at a height of 80 metres with control mechanisms like yaw control and pitch control. With this modern wind energy systems, exploitation of wind energy at low wind speeds is not possible, operation and maintenance and yaw control are difficult. In other fact, environmental problems related to disturbance in signals and birds life are considerably high. Considering all the difficulties that are faced with modern wind energy systems, a new approach for extracting wind energy is studied here. In this paper, design and experimental setup of funnel based wind energy harvesting system (FBWEHS) is explained in detail. For studying the feasibility of this new approach, a subsonic wind tunnel testing is carried out. Further smoke test in the wind tunnel is also carried out for visualizing the flow of air into the nested funnel. The results of wind tunnel testing showed the performance of the FBWEHS, in which the velocities at the turbine section is increased by a venturi speed ratio of 1.80 to 3.22 than the inlet velocities at nested funnel. Power availability at the turbine section is also increased with increase in velocity than the power available at the nested funnel. Experimental setup of FBWEHS with a propeller blade of diameter 7 cm coupled with a small size generator is used for generating power. Generated power is in the range of 0.0001 W to 9.93 W over a range of wind velocities at funnel inlet as 0.5 m/s to 7.89 m/s. With this, FBWEHS is feasible to generate more power than modern wind turbines under similar conditions of wind turbine swept area and the wind velocities by eliminating the yaw control.